2004
DOI: 10.1007/s10333-004-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of on-farm water saving irrigation techniques on rice productivity and profitability in Zhanghe Irrigation System, Hubei, China

Abstract: To optimize the use of limited water resources, surface irrigation systems in parts of China have introduced a new water saving irrigation method for rice termed alternate wetting and drying (AWD). The basic feature of this method is to irrigate so that the soil alternates between periods of standing water and damp or dry soil conditions from 30 days after crop establishment up to harvesting. However, many Chinese rice farmers still practice the continuous irrigation method with late-season drying of the soil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 2 publications
(2 reference statements)
3
34
0
Order By: Relevance
“…It is estimated that by 2002 this practice has been adopted on 40% of the rice growing area or 12 million ha in China (Li and Barker 2004). Research results have shown that farmers in ZID practiced AWD primarily in years of low rainfall or shortage of water supplied by ZIS but that AWD could be practiced without loss in yield (Belder et al 2004;Cabangon et al 2004;Belder et al 2005;Moya et al 2004). Bouman et al (2007) with research along the Yellow River concluded that most water savings under AWD came from a reduction in percolation rates.…”
Section: Periodmentioning
confidence: 97%
“…It is estimated that by 2002 this practice has been adopted on 40% of the rice growing area or 12 million ha in China (Li and Barker 2004). Research results have shown that farmers in ZID practiced AWD primarily in years of low rainfall or shortage of water supplied by ZIS but that AWD could be practiced without loss in yield (Belder et al 2004;Cabangon et al 2004;Belder et al 2005;Moya et al 2004). Bouman et al (2007) with research along the Yellow River concluded that most water savings under AWD came from a reduction in percolation rates.…”
Section: Periodmentioning
confidence: 97%
“…Highly divisible and low cost technologies have been more successfully adopted at the household level. At the community level such practices are adopted on a limited scale, due partly to policy failures and constraints to adoption such as information and financial support, extension programs, coordination failure in collective action, and the need for large fixed investments (Moya et al, 2004). The scope for increasing field level water savings and water productivity in rice production remains substantial.…”
Section: Water Resources Managementmentioning
confidence: 98%
“…The government has promoted the adoption of water saving technologies and provided financial support for infrastructure, with notable impacts on food security (Li, 2006). For instance, wet/dry irrigation for rice has positive impacts on yields, water productivity, fertilizer use efficiency and irrigation costs and returns (Moya et al, 2004). The Fig.…”
Section: Water Resources Managementmentioning
confidence: 99%
“…Studies have shown (Mushtaq et al, 2006;Moya et al, 2004;Li and Barker, 2004; Belder et al , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 13 2004) that AWD irrigation practices save 5-30% of water without adversely affecting yields. The water saving would result in decreased pumping costs, reduced energy inputs and ultimately an increase in profits.…”
Section: Water Productivitymentioning
confidence: 99%
“…This is because of the adoption of water-saving irrigation practices, in particular alternate wetting and drying (AWD) (Bouman et al, 2007;Cabangon et al, 2004). The basic feature of the AWD method is to irrigate so that the soil alternates between periods of standing water and damp or dry soil conditions from 30 days after crop establishment up to harvesting (Moya et al, 2004). In general, rice grown on tubewell has higher water productivity (0.95 kg/m 3 ) than canal irrigation (0.84 kg/m 3 ), due to more timely and flexible water supply, which not only helped in reducing the irrigation water quantity but also increased yield (Figure 9).…”
mentioning
confidence: 99%